2019
DOI: 10.1136/flgastro-2019-101176
|View full text |Cite
|
Sign up to set email alerts
|

Recognising eosinophilic oesophagitis as a cause of food bolus obstruction

Abstract: BackgroundEosinophilic oesophagitis (EoE) is a chronic, inflammatory condition of the oesophagus, characterised by intermittent dysphagia, food bolus obstruction (FBO) and histologically proven, eosinophil-mediated inflammation. EoE is identified in up to 50% of FBO presentations.ObjectiveTo evaluate the management of patients presenting with FBO to our centre against current clinical guidelines.DesignA retrospective analysis of acute FBO was performed between January 2008 and August 2014. Patients were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…18 A further retrospective study of 202 patients, who had endoscopy for foreign body impaction, reported that 26% of those who had oesophageal biopsies had EoE. 19 Patients with EoE also commonly present with dysphagia. In a prospective series of 400 patients undergoing endoscopy for oesophageal symptoms, 7.3% had histological evidence of EoE.…”
Section: Clinical Presentationmentioning
confidence: 99%
See 1 more Smart Citation
“…18 A further retrospective study of 202 patients, who had endoscopy for foreign body impaction, reported that 26% of those who had oesophageal biopsies had EoE. 19 Patients with EoE also commonly present with dysphagia. In a prospective series of 400 patients undergoing endoscopy for oesophageal symptoms, 7.3% had histological evidence of EoE.…”
Section: Clinical Presentationmentioning
confidence: 99%
“… 18 A further retrospective study of 202 patients, who had endoscopy for foreign body impaction, reported that 26% of those who had oesophageal biopsies had EoE. 19 …”
Section: Clinical Presentationmentioning
confidence: 99%
“…As the #FGDebate continued, the discussion progressed from managing food bolus obstructions to investigating and treating the underlying pathology, which can be found in over 75% of cases. Peptic strictures are the most common cause (>50%), followed by EoE in almost 40% of cases 1 5. EoE is the most common cause of food bolus obstruction in patients under the age of 50 years.…”
Section: Eosinophilic Oesophagitismentioning
confidence: 99%
“…The article by Ntuli et al published in this journal5 emphasises the variability of the clinical management of FBO and discusses the significant divergence from ‘ideal’ practice among various craft groups. With resolution of FBO, consideration of the underlying aetiology should inform commencement of treatment.…”
mentioning
confidence: 99%
“…In the era of increased EoE recognition, biopsies have been advocated at the time of food bolus removal 3. Of concern, excluding all repeat presentations and considering all patients at first presentation, is that some 276 individuals presented with FBO, yet only 25 (9.1%) were diagnosed with EoE; 4 (1.4%) had a known diagnosis of EoE, with a novel diagnosis of EoE made in 21 (7.6%) subjects 2 5. Given that EoE is now recognised as a major and common cause of FBO,6 it is likely that many cases were missed in this cohort of patients presenting with FBO.…”
mentioning
confidence: 99%